The Status of Property Granted in The Provisions of Bankruptcy Law in Indonesia - Suryanti, Nyulistiowati; Yuanitasari, Deviana; Kusmayanti, Hazar (Magister of Law, Faculty of Law, University of Mataram, 2025)
In carrying out their obligations to pay debts, Debtors often make various efforts to avoid having their assets being included in the guarantee of payment. Moreover, Debtors occasionally contrive, by providing grants, their assets in the bankruptcy decision to not be subsumed in the bankruptcy court. The aim of this research is to analyze how the arrangements for giving grants made by Bankrupt Debtors are reviewed from the Civil Code and Bankruptcy law as well as the role of the Curator in protecting Creditors and Debtors in the bankruptcy process. This research uses a normative juridical approach, where library data or secondary data is the main data, in addition to being supported by field data. The research results show that in the context of bankruptcy law, grants are an action that must be paid close attention because it can be said to be a legal action that is not required. If the Debtor gives away assets before being declared bankrupt, it can be indicated as an effort to avoid confiscation of collateral by the court. The curator has the authority to include a gift in the list of bankruptcy estates that will be sold to pay the debtor’s debts to his creditors. In such cases, the Curator can file an Actio Pauliana lawsuit with the commercial court to cancel the gift so that the assets can be included in the bankruptcy estate list. This study provides a focused examination on the legal status of gratuitous transfers in Indonesian bankruptcy law—a subject that, despite its practical urgency, remains underexplored compared to broader studies on bankruptcy proceedings or creditor protections.